2012
DOI: 10.1002/aqc.2318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea‐level rise on northern elephant seal breeding habitat at Point Reyes Peninsula, California

Abstract: 1. Northern elephant seals (Mirounga angustirostris) historically experienced a significant population decrease to the brink of extinction owing to human exploitation, but have since recovered and recolonized former breeding/haul-out sites. Point Reyes Peninsula, California, is one location where population increase has resulted in colony expansion.2. Initial models identified suitable breeding haul-outs and suggested that human disturbance, geomorphology, mean wave height, and slope were important explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…This observation may be best explored with higher resolution methods that have the capacity to capture the curviness of features (Guo et al, 2017). Habitat losses with SLR are seen for a variety of species and types of coastal ecosystems (Funayama et al, 2013;Pike, Roznik & Bell, 2015;Cloern et al, 2016).…”
Section: Sea-level Risementioning
confidence: 99%
See 3 more Smart Citations
“…This observation may be best explored with higher resolution methods that have the capacity to capture the curviness of features (Guo et al, 2017). Habitat losses with SLR are seen for a variety of species and types of coastal ecosystems (Funayama et al, 2013;Pike, Roznik & Bell, 2015;Cloern et al, 2016).…”
Section: Sea-level Risementioning
confidence: 99%
“…Increasing inundation from sea‐level rise and storm enhanced water levels are projected to change coastal habitats (Grigg et al, 2009; Karl, Melillo & Peterson, 2009; Parris et al, 2012; Funayama et al, 2013). These phenomena are already being observed in coastal areas (Tebaldi, Strauss & Zervas, 2012; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Noatak National Preserve, climate change shifted boreal conifer forest northward onto formerly treeless tundra between 1800 and 1990 (Suarez et al 1999). (Funayama et al 2013). An analysis of 22 coastal national parks indicated that the parks along the Atlantic Ocean were most at risk from sea level rise (Pendleton et al 2010).…”
Section: Historical Impacts In Us National Parksmentioning
confidence: 99%